2015
DOI: 10.15414/jmbfs.2015.4.special1.62-64
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Rosa Canina Flowers Against Selected Microorganisms

Abstract: Keywords: Bacteria, microscopic filamentous fungi, antimicrobial activity, flowers of Rosa canina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Moreover, antimicrobial effects of ethanolic and methanolic extracts of RhO have been evaluated and the results were promising (Olech et al, 2017;Talib & Mahasneh, 2010;Vlaicu et al, 2017;Yi et al, 2007). For example, Rovnã et al (2015) investigated the antibacterial effects of ethanolic and methanolic extracts of RhO on Escherichia coli, Pseudomonas aeruginosa, Aspergillus niger, Fusarium culmorum, and Alternaria alternata, and the results showed high effectiveness of the ethanolic extract on all evaluated microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antimicrobial effects of ethanolic and methanolic extracts of RhO have been evaluated and the results were promising (Olech et al, 2017;Talib & Mahasneh, 2010;Vlaicu et al, 2017;Yi et al, 2007). For example, Rovnã et al (2015) investigated the antibacterial effects of ethanolic and methanolic extracts of RhO on Escherichia coli, Pseudomonas aeruginosa, Aspergillus niger, Fusarium culmorum, and Alternaria alternata, and the results showed high effectiveness of the ethanolic extract on all evaluated microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Its leaves consist of tannins, flavonoids, and phenolic and iridoid glucosides, which confer antioxidative and antimicrobial activity 14 . The pseudo‐fruit of dog rose ( Rosa canina ) contains high levels of phenolic and flavonoid compounds, and the methanolic and ethanolic extracts of its flower have shown antibacterial activity 15 . Pomegranate fruit is widely dispersed in several tropical and subtropical countries and, despite being consumed mainly as a raw food, has recently become industrialized, generating a variety of products 16 …”
Section: Introductionmentioning
confidence: 99%
“…14 The pseudo-fruit of dog rose (Rosa canina) contains high levels of phenolic and flavonoid compounds, and the methanolic and ethanolic extracts of its flower have shown antibacterial activity. 15 Pomegranate fruit is widely dispersed in several tropical and subtropical countries and, despite being consumed mainly as a raw food, has recently become industrialized, generating a variety of products. 16 The aim of this study was to evaluate the antimicrobial activity of commercial essential oils and natural plant extracts against L. monocytogenes in a ham-based model at 0.93 and 0.95 a w values.…”
Section: Introductionmentioning
confidence: 99%
“…Rosa canina L. (Rosaceae; RC) is one of the Mediterranean traditional medicinal herbs, the ripe fruits of which contain high phenolic and flavonoid contents, fatty acids, carotenoids, ascorbic acid, triterpenes and minerals, including K, P, Mg, Ca and Fe (Demir & Özcan, ; Montazeri, Baher, Mirzajani, Barami, & Yousefian, ). Studies have shown that RC has different therapeutic properties, including antioxidant, anti‐inflammatory, anti‐diabetic, antimicrobial, anti‐cancer and immunomodulatory effects (Chrubasik, Roufogalis, Müller‐Ladner, & Chrubasik, ; Fattahi, Jamei, & Hosseini Sarghein, ; Jiménez et al., ; Orhan, Hartevioğlu, Küpeli, & Yesilada, ; Rovná, Petrová, Terentjeva, Cerná, & Kacániová, ; Tayefi‐Nasrabadi, Sadigh‐Eteghad, & Aghdam, ). Rosa canina has been used traditionally as tea for treatment of viral infections and influenza, prevention and alleviation of different ailments, such as rheumatic diseases, diabetes, inflammation, gout, kidney disorders, sciatica, fever and cold (Rahimi, Sadigh‐Eteghad, Dehnad, Mahmoudi, & Baradaran, ; Sadigh‐Eteghad et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that RC has different therapeutic properties, including antioxidant, anti-inflammatory, anti-diabetic, antimicrobial, anti-cancer and immunomodulatory effects (Chrubasik, Roufogalis, Müller-Ladner, & Chrubasik, 2008;Fattahi, Jamei, & Hosseini Sarghein, 2012;Jiménez et al, 2016;Orhan, Hartevioglu, Küpeli, & Yesilada, 2007;Rovná, Petrová, Terentjeva, Cerná, & Kacániová, 2015;Tayefi-Nasrabadi, Sadigh-Eteghad, & Aghdam, 2012). Rosa canina has been used traditionally as tea for treatment of viral infections and influenza, prevention and alleviation of different ailments, such as rheumatic diseases, diabetes, inflammation, gout, kidney disorders, sciatica, fever and cold (Rahimi, Sadigh-Eteghad, Dehnad, Mahmoudi, & Baradaran, 2017;Sadigh-Eteghad et al, 2011).…”
mentioning
confidence: 99%